EU Company Taxation in Case of a Common Tax Base: A Computer-based Calculation and Comparison Using the Enhanced Model of the European Tax Analyzer - Thorsten Stetter; Christoph Spengel; Otto H. Jacobs; Carsten Wendt (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2005)
Within the EU the relation between financial and tax accounting will be significantly influenced by the regulation adopted in June 2002 that obliges all listed companies to prepare their consolidated accounts according to International Accounting Standards / International Financial Reporting Standards (IAS/IFRS). Since dependency of financial and tax accounting according to different degrees prevails in all EU member states a linkage between IAS/IFRS and tax accounting seems to be possible. Compared to national GAAP the advantage of IAS/IFRS as a starting point for tax accounting derives from the advantages of the creation of a common tax base in the EU. However, the adoption of IAS/IFRS has to be restricted to those standards that are convenient for tax purposes. In particular, this means that tax accounting still has to follow the realisation principle as a general principle; the IAS/IFRS ?fair value-accounting? therefore cannot be adopted for tax purposes. In this paper we present estimates for the consequences of IAS/IFRS-based tax accounting on the comparative effective tax burdens of companies in 13 countries (Austria, Belgium, the Czech Republic, France, Germany, Hungary, Ireland, Latvia, the Netherlands, Poland, Slovakia, the United Kingdom, and the USA). Therefore, certain provisions of IAS/IFRS were considered as a starting point for the tax base. The effective tax burdens are calculated on the basis of the European Tax Analyzer model which was enhanced for the purposes of this study. A further question arises as to what extent an exclusive harmonisation of the tax base will effectively reduce the current EU-wide differences of effective company tax burdens. It turns out that a common tax base cannot alleviate the current EU-wide differences of effective company tax burdens. A major finding of our study reveals that the effective tax burdens in all countries considered here (except Ireland) tend to increase slightly since the tax bases tend to become broader. This offers the possibility to member states to reduce the nominal tax rate leaving the overall effective tax burden unchanged. A tax policy of tax cut cum base broadening would not only tend to increase the attractiveness of the member states as a location for companies. At the same time, this would reduce dispersions of effective tax burdens across industries. Therefore, such a tax policy is in line of the long term Community goals to become more competitive in international terms.
Keywords: H25; H21; 330; International Company Taxation; Effective Tax Burden; Tax Accounting; International Accounting Standards; Unternehmensbesteuerung; Steuerbilanz; International Financial Reporting Standards; EU-Bilanzrecht; Steuerbemessung; Steuerbelastung; EU-Staaten